A cross-sectional analysis of association between visceral adiposity index and serum anti-aging protein Klotho in adults - Cui, Jianwei; Yang, Zhenzhen; Wang, Jiahao; Yin, Shan; Xiao, Yunfei; Bai, Yunjin; Wang, Jia (Frontiers in Endocrinology, 2023)
Background: The visceral adiposity index (VAI) is regarded as a reliable indicator to assess body fat distribution and dysfunction. Klotho protein is a hormone with anti-aging biological functions. However, the relationship between them has not been researched. Objects: This study aimed to evaluate the association between VAI and serum anti-aging protein klotho in American adults. Methods: A cross-sectional study of participants was conducted based on the National Health and Nutrition Examination Surveys (NHANES) 2007–2016. Visceral adiposity was determined using the VAI score, while the klotho protein concentration was measured by ELISA kit. After adjusting some possible confounding variables, multivariate regression model was conducted to estimate the relationship between VAI and klotho protein. Furthermore, the smooth curve fitting and the segmented regression model were applied to examine the threshold effect and to calculate the inflection point. Results：In total, 6 252 adults were eligible, with a mean VAI of 2.04±0.03 and a mean klotho protein concentration of 848.79 ± 6.98 pg/ml. Multivariate regression analysis indicated that serum klotho protein concentration was lower in participants with high VAI score. When VAI was divided into quartiles, participants in the fourth quartiles of higher VAI had lower klotho protein levels (Q4: -32.25 pg/ml) than participants in the lowest quartile (Q1) after full adjustment (P ＜ 0.05). Segmented regression suggested that the turning point value of VAI was 3.21. A 1-unit increase in VAI was significantly associated with lower klotho protein levels by -18.61 pg/ml (95% CI: -28.87, -8.35; P ＜ 0.05) when VAI ranged from 0.29 to 3.21(accounting for 83.7% of the participants), however, the association was not significant when VAI ranged from 3.21 to 11.81 (P = 0.77). Conclusion: There was a nonlinear correlation between VAI score and the serum anti-aging protein klotho concentrations, showing a saturation effect. When VAI was less than 3.21, they were negatively correlated, and when VAI was greater than 3.21, they had no obvious correlation.